Overcoming malnutrition: is there an ecoregional dimension? - Sharma, Manohar; Garcia, Marito; Qureshi, Aamir; Brown, Lynn R. (International Food Policy Research Institute, 1996)
Agroecological conditions largely determine the production potential of an agrarian area and its ability to support a number of people. It seems to make sense, therefore, to base economic and policy research on ecoregional zones, rather than on geographical or political boundaries alone. This paper represents a first attempt to map the prevalence of underweight children by ecoregions, using malnutrition as a proxy for poverty. It indicates that the natural environment does play a role in poverty and malnutrition, but other socioeconomic factors have a strong influence. For example, much of Latin America and the Caribbean falls into ecoregions where children are prone to malnutrition, but the share of malnourished children is lower than would be expected because incomes are relatively high.